Lessons learnt?. (2nd February 2021) - Willis, Richard
Abstract : The Spanish Flu epidemic of 1918 claimed the lives of more than 50 million worldwide and robbed vast numbers of children of their futures. Richard Willis draws a comparison with coronavirus.